Association between functional EGF+61 polymorphism and glioma risk - Costa, BM (2007)
PURPOSE: Epidermal growth factor (EGF) plays a critical role in cancer. A polymorphism in the EGF gene (EGF+61) may influence its expression and contribute to cancer predisposition and aggressiveness. In the present study, we aimed to elucidate the role of EGF+61 in glioma susceptibility and prognosis. EXPERIMENTAL DESIGN: A case-control study involving 197 glioma patients and 570 controls was done. Univariate and multivariate logistic regression analyses were used to calculate odds ratio (OR) and 95% confidence intervals (95% CI). False-positive report probability was also assessed. The luciferase reporter gene assay was used to ascertain the functional consequences of this polymorphism. RESULTS: Corroborating the univariate analysis, the multivariate model showed that the G allele conferred higher risks for gliomas (OR, 1.32; 95% CI, 1.04-1.67), glioblastomas (OR, 1.47; 95% CI, 1.02-2.10), and oligodendrogliomas (OR, 1.55; 95% CI, 1.07-2.23). The GG genotypes were associated with increased risk for gliomas (OR, 1.71; 95% CI, 1.07-2.73), glioblastomas (OR, 2.03; 95% CI, 1.02-4.05), and oligodendrogliomas (OR, 2.72; 95% CI, 1.18-6.28). In addition, the AG+GG genotypes were associated with higher risk for gliomas (OR, 1.52; 95% CI, 1.03-2.23) and oligodendrogliomas (OR, 2.80; 95% CI, 1.35-5.79). No significant association was observed between the EGF+61 polymorphism and glioblastoma or oligodendroglioma patients' overall survival. The luciferase reporter gene assay exhibited a significant increased promoter activity for the G variant compared with the reference A allele. CONCLUSIONS: These findings support the role of the EGF+61 polymorphism as a susceptibility factor for development of gliomas and show its implication on EGF promoter activity.